Knowledge, attitudes and beliefs towards management of men with locally advanced prostate cancer following radical prostatectomy: an Australian survey of urologists. (April 2016) - Brown, Bernadette; Young, Jane; Kneebone, Andrew B; Brooks, Andrew J; Dominello, Amanda; Haines, Mary
Abstract : Objective: To investigate Australian urologists' knowledge, attitudes and beliefs, and the association of these with treatment preferences relating to guideline‐recommended adjuvant radiotherapy for men with adverse pathologic features following radical prostatectomy. Subjects and methods: A nationwide mailed and web‐based survey of Australian urologist members of the Urological Society of Australia and New Zealand (USANZ). Results: 157 surveys were included in the analysis (45% response rate). Just over half of respondents (54%) were aware of national clinical practice guidelines for the management of prostate cancer. Urologists' attitudes and beliefs towards the specific recommendation for post‐operative adjuvant radiotherapy for men with locally advanced prostate cancer were mixed. Just over half agreed the recommendation is based on a valid interpretation of the underpinning evidence (54.1%, 95% CI [46%, 62.2%]) but less than one third agreed adjuvant radiotherapy will lead to improved patient outcomes (30.2%, 95% CI [22.8%, 37.6%]). Treatment preferences were varied, demonstrating clinical equipoise. A positive attitude towards the clinical practice recommendation was significantly associated with treatment preference for adjuvant radiotherapy (rho = 0.520, P < 0.0001). There was stronger preference for adjuvant radiotherapy in more recently trained urologists (registrars) while preference for watchful waiting was greater in more experienced urologists (consultants) (b = 0.156, P = 0.034; 95% CI [0.048, 1.24]). Urologists' attitudes towards clinical practice guidelines in general were positive. Conclusion: There remains clinical equipoise among Australian urologists in relation to adjuvant radiotherapy for men with adverse pathologic features following radical prostatectomy.